PENGARUH PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN WAFER RICHEESE NABATI PADA PT. PINUS MERAH ABADI DI TANGERANG SELATAN - Andriyani, Yolla; Haryantini (Journal of Research and Publication Innovation, 2024)
This research aims to find out how promotion and brand image influence purchasing decisions for PT Pinus Merah Abadi vegetable wafers. This research method uses quantitative research methods with a population and sample of 97 consumer. The sampling technique used was a saturated sample. The data collection method used was a questionnaire. This research obtained partial results that promotion has a positive and significant effect on purchasing decisions. Based on the results of the first hypothesis test obtained from the tcount value of the hypothesis test, the value tcount > ttable (7.195> 1.661) and the results of the simple regression test Y = 11.223 + 0.626 0.05). Thus, H0 is rejected and H1 is accepted, this shows that partially the brand image variable has a significant influence on purchasing decisions for PT Pinus Merah Abadi vegetable Richesee wafers. Based on the results of the second hypothesis test obtained from the value tcount > ttable or (10.949 > 1.661) and the results of the simple regression test Y = 3.835 + 0.821 X2. This can also be strengthened with a sig value < 0.05 or (0.000 < 0.05). Thus H0 is rejected and H2 is accepted. This shows that partially the brand image variable has a significant influence on the decision to purchase vegetable Richesee wafers at PT. Everlasting Red Pine. Based on the results of hypothesis testing, the value Fcount > Ftable or (61.896> 2.701) was obtained and the results of double linear (Y) = 6.247 + 0.250 (X1) + 0.636(X2). Thus, H0 is rejected and H3 is accepted, this shows that simultaneously the promotional variables and brand image have an influence on purchasing decisions at wafer richesee PT Pinus Merah Abadi.